HUBUNGAN KADAR HEMOGLOBIN DENGAN FUNGSI KOGNITIF, KUALITAS TIDUR DAN LAMA RAWAT INAP PASIEN LANJUT USIA DI RSUP PROF. DR. R. D. KANDOU MANADO - Palawe, Prastika C.; Rotty, Linda W. A. (e-CliniC, 2016)
Abstract: One of the benchmarks to evaluate nationsâ€™ development is its life expectancy. Indonesian life expectancy is increasing along with its standards of living and health care. However, it results an increasing number of elderly patients with their multipathology characteristics. This study aimed to obtain the correlation between hemoglobin level (X) with cognitive function (Y1), sleeping quality (Y2) and length of stay (Y3) among elderly patients in Department of Internal Disease Geriatric Division at Prof. Dr. R. D. Kandou Hospital Manado period January 2013 to December 2014. This study was conducted on 180 elderly patients (according to the database). This study used secondary data obtained from the medical records. The correlation test Spearman Rank showed that the relationship between hemoglobin level and cognitive function had an r value = 0.004 and a p value sig = 0.957. The correlation between hemoglobin level and sleeping quality had an r value = -0.023 and a p value sig = 0.754. The correlation between hemoglobin and length of stay had an r value = -0.177 and a p value sig = 0.018. Conclusion: There was no correlation between hemoglobin level and cognitive function as well as sleeping quality. There was a very weak negative correlation between hemoglobin level and length of stay of elderly patients at Prof. Dr. R. D. Kandou Hospital Manado. Keywords: hemoglobin level, cognitive function, sleeping quality, length of stay Â Abstrak: Salah satu tolak ukur kemajuan suatu bangsa seringkali dilihat dari harapan hidup penduduknya. Usia harapan hidup orang Indonesia semakin meningkat seiring dengan meningkatnya taraf hidup dan pelayanan kesehatan dengan konsekuensi meningkatnya jumlah pasien lanjut usia dengan karakteristik multipatologi. Penelitian ini bertujuan untuk memperoleh analisis hubungan kadar hemoglobin (X) dengan fungsi kognitif (Y1), kualitas tidur (Y2) dan lama rawat inap (Y3) pasien lanjut usia di Bagian Ilmu Penyakit Dalam Divisi Geriatri RSUP Prof. DR. R. D. Kandou Manado periode Januari 2013 sampai Desember 2014. Penelitian ini dilakukan pada 180 pasien lanjut usia (berdasarkan database). Pengambilan data sekunder (retrospektif) diperoleh dari catatan medik. Uji korelasi Spearman Rank untuk analisis hubungan kadar hemoglobin dan fungsi kognitif mendapatkan nilai r = 0,004 dan nilai p sig = 0,957. Hubungan kadar hemoglobin dan kualitas tidur mendapatkan nilai r = -0,023 dan nilai p sig = 0,754. Hubungan kadar hemoglobin dengan lama rawat inap mendapatkan nilai r = - 0,177 dan nilai p value sig = 0,018. Simpulan: Pada pasien lanjut usia di RSUP Prof. Dr. R. D. Kandou Manado tidak terdapat hubungan antara kadar hemoglobin dengan fungsi kognitif dan kualitas tidur. Terdapat hubungan negatif yang sangat lemah antara kadar hemoglobin dengan lama rawat inap pasien. Kata kunci: kadar hemoglobin, fungsi kognitif, kualitas tidur, lama rawat inap.